Complaint According to Provisions of Code of Civil Procedure from 1865 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
In civil law, a complaint is the very first formal action taken to officially begin a lawsuit. It contains the allegations against the defense, the specific laws violated, the facts that led to the dispute, and any demands made by the plaintiff to restore justice. If a complaint is incomplete in a way that it does not comprise all the necessary facts and legal reasons sufficient to support a claim against the defendant, it can lead to judicial errors and breaches of laws. That is a reason why precise and detailed legal regulation regarding initial document in a lawsuit is of great significance for plaintiff′s success in litigation. The author of Code of Civil Procedure from 1865 was fully aware of this fact and therefore complaint was meticulously regulated in 23 paragraphs. As these provisions were in all respects satisfactory, they were not amended during the whole period that the Code was in force. Minister of Justice Stojan Veljković, however, proposed amendments to a few paragraphs concerning complaint in his draft from 1872 but, since this document was never enacted, aforementioned provisions remained unrevised.